Blended learning, Active Learning Classroom and information literacy in higher military education - Larsson, Anna-Karin; Gullberg, Sonja; Ekstrand, Malin (Septentrio Conference Series, 2020)
How the learning environment is designed is an important part of creating good conditions for a professional education. The design of the physical and the online learning environment affects what students are expected to do in these spaces (Leijon 2016). A learning environment designed for student activity creates better conditions for activity, while an environment designed for instruction gives a different signal. A so-called Active Learning Classroom (ALC) can encourage student activity and increased learning. In an ALC environment, students become co-creators of knowledge. (Rands & Gansemer-Topf, 2017) It is impossible to know what competencies needed for the future. Therefor it is important to create a learning environment that support critical reflection, collaboration, creativity and innovation (Barnett, 2004). Flexible learning or blended learning aims to combine the strengths of online learning activities with those conducted on campus. There is a variety of ways to combine online learning activities with those conducted in the physical classroom (Vaughan, Cleveland & Garrison, 2013). For example, flipped classroom, podcast and peer learning. Adequate ICT pedagogical support can stimulate and find ways to expand the pedagogical palette with various creative online learning activities. During the round table discussion, we want to discuss the possibilities of using online learning activities, online examination and Active Learning Classroom to promote information literacy. The questions we want to discuss are: How can we combine online learning with facilitating information literacy and ALC? In what way do student’s expectations of teaching and learning affect the implementation of online learning and ALC? How can we collect student experiences of teaching online and in ALC? How can information literacy support learning and subject knowledge in higher military education?